Usmeni stil djela A. A. Barića Statistica Europae (1792) - Jovanović, Neven (2003)
Adalbert Adam Barić (1742--1813) was a university professor first in Zagreb, Croatia, and later in Pest, Hungary ; both countries were then parts of the Habsburg Monarchy. Barić's main field was political science (then called statistics) ; his Latin text Statistica Europae (1792) is a historic, geographic, economic, and political description of four European states: Spain, Portugal, the Netherlands, and Great Britain. Barić, a representative of the Enlightenment, seems to have chosen these four states to serve as positive and negative models for further development of Hungarian Kingdom ; the students of statistics were the future administrators and officials of this state. The Statistica Europae was not published (until recently, in 2001--2002) ; Barić did not intend this text for publication. This is, in fact, a collection of Barić's university lectures. This makes Statistica Europae a neo--Latin text prepared for public oral performance, a meeting point of written and spoken 18th century neo--Latin idiom. What traces of orality do we recognize in the Statistica Europae? For instance: very long and intricate clause complexes, combined with repetition of key words ; grammatical variation greater than lexical ; frequent anacolouthon ; switching of person in the middle of a clause.
Projekt MZOS
ENG